The Professionalism of Treasurers Managing Education Unit Operational Assistance Funds (Study in East Bolaang Mongondow Regency) - Selamat, Mosrion; Wawointana, Thelma; Mokat, Jetty E. H. (Technium Social Sciences Journal, 2025)
This study aims to determine, analyze and describe the professionalism of treasurers managing Education Unit Operational Assistance (BOSP) funds in East Bolaang Mongondow Regency. The professionalism of the treasurer is a crucial aspect in ensuring accountability, transparency, and effectiveness in the use of education funds. The research method used was a qualitative method with a descriptive qualitative approach with data collection techniques through interviews, observations and documentation studies. The research sample amounted to 10 people who were determined using purposive sampling technique. The results showed that the professionalism of the treasurers was not optimal, most of the treasurers had carried out their duties in accordance with applicable regulations, but there were still some obstacles such as lack of technical training, limited understanding of the latest regulations, and delays in fund disbursement which had an impact on the effectiveness of budget management. This study recommends capacity building through continuous training and a more structured monitoring and evaluation system to improve the performance of school treasurers.